Langerhans' Cell Histiocytosis Masquerading as Caroli's Disease. Issue 7 (October 2020) - Narayanasamy Rajavelu, Thiagarajan; Abimannane, Anitha; Chinnaiah Govindhareddy, Delhi Kumar; Kayal, Smita; Kar, Rakhee
Abstract : Langerhans' cell histiocytosis is an uncommon disease in children with varied clinical presentation. Multisystem form of this disorder usually affects organs like the bones, skin, liver, spleen, lungs, and the central nervous system. We describe here the clinical details of a 2-year-old girl with involvement of unusual sites like the parotid glands and the nails. This child also had multiple cystic lesions in the liver leading to a misdiagnosis of Caroli's disease. Knowledge about the uncommon manifestations of this rare disorder helps in early diagnosis and treatment. Abstract : Supplemental Digital Content is available in the text.